DEVELOPMENT OF PORPHYRIN-ACRIDINE HYBRID COMPOUNDS AS B-DNA BINDERS AND DNA TOPOISOMERASE II ALPHA INHIBITORS: AN IN SILICO STUDY - Nashrullah Muhammad, Hubbi
Porphyrin compounds have been known to accumulate in tumor cells and bind strongly to DNA through several modes of interaction and are thus potential candidates for anticancer agents. Several research have proven that porphyrins are able to trigger cell death through DNA damage and/or changes in duplex DNA conformation. Furthermore, several studies suggest that porphyrins may trigger cell death through other means, including through interactions with enzymes essential to cell replication. In this in silico study, the potential for porphyrin derivate compounds to interact and inhibit duplex DNA and DNA Topoisomerase II alpha was investigated. Porphyrin-acridine conjugate compounds were designed in order to improve the compounds’affinity towards the two macromolecular targets studied. Acridine was chosen as the conjugate moiety due to its ability to strongly bind to DNA and has shown characteristics of cytotoxicity. Ten porphyrin-acridine (PA) compounds were designed, and their affinity towards duplex DNA and modes of interaction were screened using molecular docking simulations. Molecular dynamics simulation techniques were then utilized to investigate further the molecular mechanisms of interaction between the PA compounds and the targets, the strength of the interactions, and the changes in DNA conformation that resulted. First, the molecular mechanics Poisson- Boltzmann surface area (MMPBSA) method was used to assess the affinity of the PA compounds towards the targets. Second, the molecular mechanism of interaction between the PA compound and duplex DNA was studied using the umbrella sampling technique of molecular dynamics simulations. Third, the effects of PA binding on DNA conformation were investigated through molecular dynamics simulations and measuring the changes in the length and curvature of DNA, and the depth and width of DNA grooves. Initial screening of the ten designed compounds resulted in three compounds with high affinity towards duplex DNA, namely h2pac, monoimp, and bispyp, and two compounds with high affinity towards the Topoisomerase II alpha active site, namely monopyp and bispzp. The interaction dynamics between the PA compounds and duplex DNA showed that h2pac and monopyp were able to form stable complexes with DNA, as shown by RMSD and RMSF analyses. Meanwhile, interaction dynamics between the PA compounds and the Topoisomerase II alpha showed that monopyp and bispzp were able to stabilize the enzyme’s active site, which is a primary characteristic of inhibitors of said enzyme. Furthermore, the binding of h2pac on the DNA minor groove also resulted in macro changes in the DNA conformation, showing the potential for the compound to disturb cellular processes that involve DNA such as replication and transcription. The results of this study as a whole shows the potential for h2pac, monopyp, and bispzp to bind strongly with duplex DNA and alter its conformation, and interact with Topoisomerase II alpha in such a way as to potentially inhibit its function and affect DNA replication.